Optimizing Media Integration for Foreign Language Acquisition: A Public Perspective - Anggraini, Rifa (Bhandar: Harvesting Community Service in Asia, 2024)
In an era dominated by rapid technological advancements, media plays a crucial role in the acquisition of foreign languages. The effective integration of media resourcesranging from digital platforms to multimedia toolscan significantly improve the language proficiency of learners and the general public. This literature review investigates the evolving role of media in foreign language education, examining its influence on learner motivation, engagement, and overall learning outcomes. By synthesizing existing studies, the article seeks to provide insights into best practices for using media in language instruction and encourages the broader public to utilize these tools for more dynamic and interactive language learning experiences. Furthermore, this review addresses the challenges of media overuse and proposes strategies for maintaining a balanced approach in the educational landscape.